A broadband circularly polarized monopole antenna for millimeter‐wave short range 5G wireless communication. Issue 2 (15th December 2020) - Kumar, Ashok; Kumar, Ashok; Kumar, Arjun
Abstract: This article describe the design and measurement of a broadband circularly polarized (CP) monopole antenna for millimeter wave short range 5G Wireless communication applications. This antenna is comprised of a T‐shaped monopole antenna with an inverted‐L grounded stub and an asymmetric coplanar wave guide feed. To attain the broadband CP, an inverted‐L grounded stub is embedded in the coplanar ground and introducing asymmetry in the horizontal T‐shaped patch connected feed line monopole antenna. A compact size of 1.877λ L  × 1.706λ L  × 0.130λ L is accomplished when measured at lower edge frequency ( f L, |S11| ). For the proposed antenna structure conforming to f L, |S11|, a measured 3‐dB axial ratio bandwidth of 13.67% (4 GHz, 27.26‐31.26 GHz), impedance bandwidth of 27.9% (8.3 GHz, 25.6‐33.9 GHz), peak gain of 7.15dBi, and a bidirectional patterns with a dual sense polarization are attained.